ANALYSIS OF ERROR IN DETERMINING THE DISTANCE BETWEEN TWO POINTS IN THE CARTESIAN PLANE IN THE FIRST SEMESTER STUDENTS - Setiawan, Yayan Eryk (Universitas Tanjungpura, 2022)
The purpose of this study is to describe the error in determining the distance between two points. This type of research is descriptive qualitative research. The subjects of this study were 6 first-semester students of the mathematics education study program at one of the universities in Malang City who experienced errors in determining the distance between two points. The research instrument consisted of the problem of the distance between two points and the interview guide. The data collected in this study were in the form of student worksheets and interviews. Student work data were analyzed based on the types of errors that aim to determine the characteristics of student errors. The results of the interviews were analyzed by coding words or sentences to find out the causes of student errors. The results showed that there were three errors in determining the distance between two points, namely: misconception caused by misunderstanding and intuitive thinking; miscalculation caused by lack of thoroughness, and fact errors caused by lack of thoroughness and lack of attention to the overall information contained in the problem.